A new species of Delphinium L. (Ranunculaceae) from Dagestan (Eastern Caucasus) - Рамазан Алибегович Муртазалиев; Александр Николаевич Луферов (Turczaninowia, 2021)
The new species Delphinium samurense Murtazaliev et Luferov (sect. Diedropetala Huth) is described from the Eastern Caucasus. The novelty is endemic to southern Dagestan (Rutul district). Its morphological differences from the closely related species D. macropogon Prokh. are shown. Distribution and ecology of the new species are characterized.